Investigation on coaxial pseudo-fault characteristics induced by the outer ring defect in the single-sided axle-box bearing of wheelset in urban rail vehicles - Wentao Zhao; Jianming Ding; Xiaokang Liao; Weiwei Liu (Scientific Reports)
Abstract An in-depth understanding of vibration characteristics of the coaxial pseudo-fault in axle-box bearings installed coaxially on both sides of the wheelset is essential for distinguishing the real fault and the pseudo-fault in axle-box bearing condition monitoring. Therefore, a bearing-vehicle-track coupled dynamic model is developed, which incorporates an axle-box bearing dynamic model with an outer ring defect and a vehicle-track coupled dynamic model. The axle-box vibration responses on both sides of the wheelset, considering single-sided bearing defects with different widths at different vehicle speeds, are obtained through simulation and subsequently analyzed. The results indicate that the coaxial pseudo-fault effect is more pronounced under a defect width of 3 mm. The amplitude, root mean square (RMS), and shock pulse method (SPM) indicators of the axle-box vibration response on the defective side exceed those on the healthy side. The impulse response transmitted to the healthy side consistently lags behind that generated on the defective side. The minimum lag time is 0.0011 s. The fault frequency components and harmonics on the healthy side are more dispersed and decay more rapidly. Finally, based on amplitude-related features and spectral energy dispersion characteristics, a criterion for identifying the coaxial pseudo-fault is proposed using the frequency variance (VF) indicator, and the rationality of the proposed indicator range is demonstrated through field test data.